Rebuilding Lives: Investigating the Consequences of the 2015 Earthquake on Family Dynamics and Resilience - Ghimire, Dipesh Kumar (Patan Pragya, 2023)
Nepal, being among the world's most disaster-prone countries, witnesses numerous fatalities resulting from calamities each year. The devastating earthquake of 2015 in Nepal claimed the lives of 8,848 individuals, left 22,307 injured, and caused the collapse of 868,042 homes. This research paper aims at delving into the repercussions of the earthquake on change in the family dynamics in Nepal. Unger and Douglas (1980) assert that families play a crucial role in facilitating adaptation to stress, providing emotional and marital support through formal and informal channels during and after disaster events. This study endeavors to ascertain the impact of the 2015 earthquake on the change in dynamics of family relationships and structures.